Validasi Nutrition Screening Tool For Childhood Cancer (SCAN) Dalam Versi Indonesia - La Saudi; Allenidekania; Nur Agustini (PT. Pubsains Nur Cendekia, 2023)
Background & objectives: Nutritional screening is very important to assess the nutritional status of children with cancer that increases nutrition or the risk of malnutrition so that it is easy to determine the right nutrition management. Aim: The Indonesian version of the Validating Childhood Nutrition Screening Tool (SCAN) as a cancer child nutrition screening tool. Method: Before being used in research this instrument was translated, then distributed to nurses oncology care rooms for openness testing. Tracking test method by comparing instruments for nutritional screening tools for child cancer (SCAN) with STRONGkids instruments in 92 children with translated cancer. Results: The SCAN instrument showed very good sensitivity, namely 100% (Cl95% 100% -100%; p <0.001), specificity: 21.4%, PPVs: 45%, and NPVs: 100%. Conclusion: This SCAN instrument is valid and can be used for pediatric patients with cancer, easily and quickly resolved when conducting a nutritional screening.